Representasi Identitas Dan Penerimaan Diri Dalam Lagu “Diri” Karya Tulus: Kajian Semiotika Charles Sanders Peirce - Muhammad Rizky; Zahrotus Sa'idah (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
The song Diri by Tulus explores the themes of identity and self-acceptance, which are highly relevant to the lives of young people in the digital era. However, the representation of identity and self-acceptance constructed through the song’s lyrics has received limited scholarly attention from the perspectives of semiotics and representation theory, making further analysis necessary to understand the meanings embedded within the lyrics. This study aims to analyze the representation of identity and self-acceptance in the lyrics of Diri by Tulus using Charles Sanders Peirce’s semiotic approach and Stuart Hall’s theory of representation. This research employed a descriptive qualitative method, with the lyrics of Diri serving as the primary data. The data were analyzed using Charles Sanders Peirce’s semiotic framework by identifying the representamen, object, and interpretant, followed by interpretation through Stuart Hall’s theory of representation to explain the process of constructing and interpreting representations of identity and self-acceptance. The findings reveal that the lyrics of Diri represent six major themes: self-acceptance, self-identity, self-appreciation, emotional healing, self-worth, and mental health. These meanings are constructed through symbols, metaphors, and reflective language that illustrate an individual’s journey of recognizing, accepting, and valuing oneself after experiencing various life events. Based on Stuart Hall’s theory of representation, meaning is constructed through language and reinterpreted by listeners according to their respective social and cultural experiences. Therefore, Diri functions not only as entertainment but also as a communication medium that represents identity, self-acceptance, and mental health in the digital era.